التحليل الاحصائي للتركيب الزواجي في محافظة بابل لعام 2015 - د. جواد كاظم عبيد الحسناوي أ. م.; عباس جاسم م. مياسة (Journal of College of Education, 2021)
The marriage a form of society that guarantees the protection of individual and family and access them to stability, whether the laws and regulations or customs and traditions of the status or religious to save the sustainability of the community, but there are variables group influenced the nature of marriage and how to understand the marital life and responsibilities, Vtbaant phenomena Marital Status, differing this contrast with differing impact of those variables. This research aims to analyze spatial relationships, marital status Boqsamaa four (singles-Metzjrn- Mtalegon- widows) by genre for males and females, according to the environment of the urban and rural areas, in the largest provinces of the Middle Euphrates populous are the province of Babylon, in terms of contrast between the administrative units and different this discrepancy during the field study for 2015 as a result of changes associated with the demographic, social, economic and educational characteristics of community study, affected by the exceptional circumstances experienced by Iraq in general are wars, economic blockade, terrorism and displacement, and the variability of these variables between urban and rural areas depending on the characteristics and the nature of each society, and based on the descriptive and analytical approach quantitative in the statistical study of the relations that have been associated phenomena Marital Status through the use of statistical methods to adopt statistical package (SPSS) as an analysis correlation and regression analysis and multi-factor identification and testing of T-test and the value of F-test and analysis of variance and Pearson correlation coefficient. The most important findings of the research low percentage of singles in 2015 to reach 45.0%, while the proportion of married couples fell in 2015 to reach 46.0%, while the divorce Mdyate dramatically increased the rate stands at 3.2% in 2015, while the ratio of widowhood 2015 amounted to 5.8%. As for the environment level has bachelors rates rose in urban areas and a decrease in the countryside, high unmarried ratios in rural areas compared to urban areas for the prevalence of early marriage, and the desire to have the largest number of boys guaranteeing public powers to him in agriculture, and the convergence of divorce and widowhood rates in urban and rural areas, but it was higher in urban areas compared to rural areas, the impact of the factors identified by the study, which concluded that there is a strong correlation between the number of bachelors in urban areas and a set of variables adopted by the demographic study, economic, social and other 99%, and in the countryside was a strong and positive relationship between the number of bachelors and those variables by 94%. The impact of these factors on married couples was a strong and positive by 99% in urban areas, including the (jobs, housing and provide rental and university certificate along with other factors) In the countryside, the relationship between the number of married couples and group variables are age and income level, and the degree of education of testimony prep and below factor King housing) strong and positive relationship confidence stood at 91%. For the analysis of the relationship between divorce and a factor variables (male, age, parents and relatives enter into married life, the lack of adequate housing, lack of work, low living standards) a strong relationship by 98%. In the countryside, the relationship has been increased by 99% between divorce and a set of variables that I mentioned study, the widowed, the numbers associated with the factor of death and there were a range of causes most pronounced in urban areas in terrorism, diseases and the relationship between them strong by 87% along with other factors less influential. While the strong relationship between widowhood, wars, accidents and other cases in the countryside rose by 96% in.